2018
DOI: 10.1186/s12885-018-4030-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective oestrogen receptor antagonists inhibit oesophageal cancer cell proliferation in vitro

Abstract: BackgroundOestrogen receptors (ER) have a well-established role to the initiation, progression and regulation of responses to treatment of breast, prostate, and lung cancers. Previous data indicates altered ER expression in oesophageal cancers (OC). However the role of ER subtypes and ER specific inhibitors in the regulation of OC progression remains unclear. This study sought to assess levels of ERα and ERβ in OC. The effects of highly selective ER antagonists on cell proliferation and apoptosis in two OC ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Previous research into sex hormone receptor expression in EAC has been sparse and contradictory (see Table 4 ). Similar to our study, earlier studies have identified positive ERβ expression [ 24 26 , 28 ] and none or limited ERα expression [ 24 , 25 ] in EAC. Additionally, in a small study of 33 patients, Liu et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous research into sex hormone receptor expression in EAC has been sparse and contradictory (see Table 4 ). Similar to our study, earlier studies have identified positive ERβ expression [ 24 26 , 28 ] and none or limited ERα expression [ 24 , 25 ] in EAC. Additionally, in a small study of 33 patients, Liu et al .…”
Section: Discussionsupporting
confidence: 92%
“…Clinical studies have shown complex patterns of ER expression in EAC specifically but few studies have been conducted and to date they have been small in size (e.g. 11–28 cases) [ 24 – 28 ]. Similarly, few studies have investigated AR expression in EAC tissue [ 27 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note the limitations of the current study, where the role of estrogen receptor was not investigated. Al-Khyatt et al [50] elegantly demonstrated that ERβ was the predominant form in both normal mucosa and esophageal cancer cells, whereas ERα was detected at a minimal level. In addition, these authors showed that the proliferation of OE33 and OE19 cell lines was does-dependently inhibited, while apoptosis was induced by an ERα-specific antagonist (MPP) and an ERβ-specific antagonist (PHTPP), establishing ESR1 and ESR2 as potential therapeutic targets for esophageal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that hormones and their ratios can be used as markers of granulosa cell apoptosis or follicular atresia (Yu et al, ) and an accelerated effect of E‐stimulated granulosa cell apoptosis. Hormone levels were regarded to be connected with cell proliferation and cell apoptosis (Al‐Khyatt, Tufarelli, Khan, & Iftikhar, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%